Pengaruh Kawasan Migas Terhadap Pola dan Struktur Ruang Perkotaan Kecamatan Kapas, Kabupaten Bojonegoro - Purnamaningsih, Dwi Ratna Putri (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Kapas Subdistrict as an oil and gas area of Sukowati Field in Tuban Block with domination of oil and gas mining sector has amount 86,62%, have changed the economic structure and livelihoods tend to tertiary sector. The changes has influences the landuse pattern in urban area of Kapas Subdistrict as a space in region where the alocation of mining area is 150 hectares. Therefore, this research was investigated the spatial influence of mining area of Sukowati Field in Tuban Block to the pattern and structure of urban space in Kapas subdistrict before and after in 2005 and 2016. The research approach use positivistic approach with quantitative method and primery data from observation, interview and secondary data in 2005 and 2016. The data was processed and presented with pictures, tables and maps using descriptive analysis, Marshal’s centrality index and superimposed technique analysis. The analysis result of landuse changed consist of residential area 22%, industrial area 2,77%, trade and services area 1,4% with the linier growth in arterial roads and a colector which is close to the mining area. The changing of space structure due to mining activities was marked by educational facilities improvement that enhance the hierarchy and service center of Ngampel and Kalianyar village from III up to II. The improvement of roads length in 2005 to 2016 are 36.706 meters to 75.440 meters which is dominated by rural roads. The pipeline network of Sukowati Field in Tuban Block in Kapas Subdistrict, Bojonegoro Regency connected with Mudi Field in Tuban Block in Soko Subdistrict, Tuban Regency along 10 kilometers trough pipeline with diameter 10 inch.